Alkali Transition Metal Phosphites as Potential Cathode Materials Grown from Molten Boric Acid. Issue 7 (21st March 2013) - Huang, Hui‐Lin; Huang, Shu‐Hao; Lai, Chun‐Wei; Wu, Jia‐Rong; Lii, Kwang‐Hwa; Wang, Sue‐Lein
Abstract This is the first study on developing six alkali transition metal phosphites as potential candidates of cathode materials grown from molten boric acid, a simple, low energy costing method compared with conventional solid‐state reactions. Li2[Mn(HPO3)2] (1) and Li[V(HPO3)2] (2) are featured with high theoretical capacitance values up to 117 and 123 mAh/g, respectively. With the replacement of Li+ by Na+ or K+, four new compounds with strongly related layer topology Na2[Co4(HPO3)5] (3), K2[Co3(HPO3)4] (4), K2[Mn2(HPO3)3] (5), and K[V(HPO3)2] (6) were prepared. The synthesis mediated by molten boric acid automatically provides reductive atmosphere and helps maintain low valence in metal centers.